Genetic polymorphisms in homologous recombination repair genes in healthy Slovenian population and their influence on DNA damage - Goričar, Katja (Radiology and oncology (Ljubljana), 2012)
Background. Homologous recombination (HR) repair is an important mechanism involved in repairing double-strand breaks in DNA and for maintaining genomic stability. Polymorphisms in genes coding for enzymes involved in this pathway may influence the ca pa city for DNA repair. The aim of this study was to select tag single nucleotide polymorphisms (SNPs) in specific genes involved in HR repair, to determine their allele frequencies in a healthy Slovenian population and their influence on DNA damage detected with comet assay. Materials and methods. In total 373 individuals were genotyped for nine tag SNPs in three genes: XRCC3 722C>T, XRCC3 -316A>G, RAD51 -98G>C, RAD51 -61G>T, RAD51 1 522T>G, NBS1 553G>C, NBS1 1197A>G, NBS1 37117C>T and NBS1 3474A>C using competitive allele-specific amplification (KASPar assay). Comet assay was performed in a subgroup of 26 individuals to determine the influence of selected SNPs on DNA damage. Results. We observed that age significantly affected genotype frequencies distribution of XRCC3 -316A>G (P = 0.039) in healthy male blood donors. XRCC3 722C>T (P = 0.005), RAD51 -61G>T IP = 0.023) and NBS1 553G>C (P = 0.008) had a statistically significant influence on DNA damage. Conclusions. XRCC3 722C> T, RAD51 -61 G> T and NBS 1 553G>C polymorphisms significantly affect the repa ir of damaged DNA and may be of clinical importance as they are common in Slovenian population.
Keywords: Age Factors; Aleli; Alleles; DNA Damage; DNA Repair; DNA, obnova; DNA, pošdkoba; Genotip; Genotype; Polimorfizem (genetika); Polymorphism (Genetics); Starostni faktorji